Pelatihan dan Pemanfaatan Teknologi Whatsapp Business Dalam Mengembangkan Penjualan Produk Pada UMKM - Eko Setia Budi; Ade Priyatna; Eva Zuraidah; Sanwani; Dito Tri Ardana; Aprilia Dimas Sahid; Ghifary Rafy Pratama; Kenji Ferdian Santosa; Muhamad Irfan (JPM: Jurnal Pengabdian Masyarakat, 2024)
UMKM Tajur Halang Makmur is a social organization as a forum and means of developing every member of society who grows and develops on the basis of awareness and social responsibility from and for the community in the region, especially those engaged in medium and small businesses. Meanwhile, the membership of Jakarta MSMEs, hereinafter referred to as PKK Mothers, is every member of the community. Tajur Halang Makmur UKM Cooperative, Founded on 03 September 2019, address Ruko Ning's Residence Jalan Raya Kalisuren, Kalisuren Village, Tajurhalang District, Bogor Regency, Deed of establishment of the cooperative "UKM Tajurhalang Makmur" Number: 04,- Date: 03 September 2019. UKM Cooperative Tajurhalang Makmur operates in the Multi Business sector. The problem is limited understanding of social media management which has not been optimized within the MSME management environment. The use of social media is still manual for sales information. Therefore, Nusa Mandiri University carries out Community Service in the form of training and utilizing Whats App Business technology in developing product sales. With this training, PKK mothers can help manage and provide information data with training in implementing digital product sales. The output that will be achieved from this socialization in the form of community service is publication in local print or electronic mass media